2008
DOI: 10.1167/iovs.07-0675
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Lysosomal pH in RPE Cells from Cultured Human and ABCA4−/−Mice: Pharmacologic Approaches and Functional Recovery

Abstract: Elevation of lysosomal pH in RPE cells interferes with the degradation of outer segments and may contribute to the pathologies associated with A2E. Pharmacologic elevation of cAMP can restore an acid pH and improve degradative function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
161
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(181 citation statements)
references
References 49 publications
11
161
0
Order By: Relevance
“…Addition of A2E to cultured RPE cells increases the lysosomal pH, slows degradation of proteins, and inhibits the translocation of protons into the lysosomes and the degradation of outer segments (3,15). Lysosomal pH in the RPE cells of ABCA4 Ϫ/Ϫ mice is elevated compared with age-matched controls (20), consistent with the alkalinizing effect of A2E.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Addition of A2E to cultured RPE cells increases the lysosomal pH, slows degradation of proteins, and inhibits the translocation of protons into the lysosomes and the degradation of outer segments (3,15). Lysosomal pH in the RPE cells of ABCA4 Ϫ/Ϫ mice is elevated compared with age-matched controls (20), consistent with the alkalinizing effect of A2E.…”
supporting
confidence: 65%
“…The human ARPE-19 cell line was obtained from American Type Culture Collection (Manassas, VA) and processed as described previously (20). In brief, cells were grown to confluence in 25-cm 2 primary culture flasks (Becton Dickinson) in a 1:1 mixture of Dulbecco's modified Eagle's medium and Ham's F-12 medium with 3 mM L-glutamine, 100 g/ml streptomycin, and 2.5 mg/ml Fungizone and/or 50 g/ml gentamicin and 10% fetal bovine serum (all Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This showed that an elevated lysosomal pH interfered with degradation of outer segments and the contribution to the N-retinylidene-N-retinylethanolaminee associated pathologies. 57 Two general strategies recently were investigated for the treatment of individuals with NCL. The identification of a master regulator of lysosomal biogenesis and autophagy, transcription factor EB, has uncovered the adaptive behavior of lysosomes in response to environmental cues as starvation.…”
Section: Discussionmentioning
confidence: 99%